LGU RETREAT: PREPARING THE UNIVERSITY FOR THE FUTURE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 31 May 2015 Universiti Sains Malaysia (USM) is making all the necessary preparations to move forward and meet the challenges ahead with more effective strategies. "When USM was given the responsibility to carry out the Accelerated Programme for Excellence (APEX) programme, there were high expectations from the government, the people and all the stakeholders that need to be met," said the Chairman of USM Board of Governors (LGU) Tan Sri Datuk Dr. Zulkefli A. Hassan.